An additional promoter within the protein-coding region of the psbD-psbC gene cluster in tobacco chloroplast DNA. - Yao, W B (1989)
Transcription of the psbD-psbC gene cluster in tobacco chloroplasts has been studied. This cluster contains in linear sequence the overlapping genes encoding the D2 and 43 kDa proteins of Photosystem II (psbD and psbC, respectively), and ORF62. Eight major transcripts ranging from 1.5 to 4.4 kb were detected by northern blot analysis. S1 mapping experiments revealed that these multiple transcripts comprise five distinct 5' ends whose precise positions were further determined by primer extension analysis. Two of the five 5' ends were determined to be the transcriptional initiation sites by in vitro capping assays: the main site is located 905 bp upstream from the ATG codon of psbD and the additional site is 194 bp upstream from the first ATG codon of psbC. The latter site and the preceding prokaryotic promoter motif are within the protein-coding region of psbD. The 3' ends of transcripts were determined by S1 mapping.